A dose response randomised controlled trial of docosahexaenoic acid (DHA) in preterm infants. (August 2015) - Collins, C.T.; Sullivan, T.R.; McPhee, A.J.; Stark, M.J.; Makrides, M.; Gibson, R.A.
Abstract: Thirty one infants born less than 30 weeks׳ gestational age were randomised to receive either 40 ( n =11), 80 ( n =9) or 120 ( n =11) mg/kg/day of docosahexaenoic acid (DHA) respectively as an emulsion, via the feeding tube, commenced within 4 days of the first enteral feed. Twenty three infants were enroled in non-randomised reference groups; n =11 who had no supplementary DHA and n =12 who had maternal DHA supplementation. All levels of DHA in the emulsion were well tolerated with no effect on number of days of interrupted feeds or days to full enteral feeds. DHA levels in diets were directly related to blood DHA levels but were unrelated to arachidonic acid (AA) levels. All randomised groups and the maternal supplementation reference group prevented the drop in DHA levels at study end that was evident in infants not receiving supplementation. Australian New Zealand Clinical Trials Registry: ACTRN12610000382077.